Green synthesis of silver nanoparticles using Prosopis juliflora bark extract: reaction optimization, antimicrobial and catalytic activities. (4th July 2018) - Arya, Geeta; Kumari, R. Mankamna; Gupta, Nidhi; Kumar, Ajeet; Chandra, Ramesh; Nimesh, Surendra
Abstract: In the present study, silver nanoparticles (PJB-AgNPs) have been biosynthesized employing Prosopis juliflora bark extract. The biosynthesis of silver nanoparticles was monitored on UV-vis spectrophotometer. The size, charge and polydispersity index (PDI) of PJB-AgNPs were determined using dynamic light scattering (DLS). Different parameters dictating the size of PJB-AgNPs were explored. Nanoparticles biosynthesis optimization studies suggested efficient synthesis of highly dispersed PJB-AgNPs at 25 °C when 9.5 ml of 1 mM AgNO3 was reduced with 0.5 ml of bark extract for 40 min. Characterization of PJB-AgNPs by SEM showed spherical-shaped nanoparticles with a size range ∼10–50 nm along with a hydrodynamic diameter of ∼55 nm as evaluated by DLS. Further, characterizations were done by FTIR and EDS to evaluate the functional groups and purity of PJB-AgNPs. The antibacterial potential of PJB-AgNPs was tested against E. coli and P. aeruginosa . The PJB-AgNPs remarkably exhibited anticancer activity against A549 cell line as evidenced by Alamar blue assay. The dye degradation activity was also evaluated against 4-nitrophenol that has carcinogenic effect. The results thus obtained suggest application of PJB-AgNPs as antimicrobial, anticancer and catalytic agents.